The effect of Plantago major cream on intensity of pain and episiotomy wound healing in nulliparous women - Bahareh Baghal; Raheleh Babazadeh; Roshanak Salari; Nahid Ghanbarzadeh; Hamid Hydarian (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2022)
Introduction: One of the medical interventions in childbirth is episiotomy which is used to widen the pelvic outlet. Plantago is one of the oldest medicinal plants that have wound healing properties due to its flavonoids and phenolic compounds. The present study was performed aimed to determine the effect of plantago cream on intensity of pain and episiotomy wound healing in nulliparous women.Methods: This triple-blind clinical trial study was performed in 2019 on 107 nulliparous women who had referred to Valiasr Hospital in Birjand for natural childbirth. The participants were randomly divided into two groups of placebo and drug. After delivery, mothers used 2-3 cm of prescribed cream on the sutures for 10 days and twice a day. The wound healing rate was evaluated on the third, seventh and tenth days after delivery using the Reda tool. Data were analyzed using SPSS 21 software and Chi-square and Mann-Whitney tests. P< 0.05 was considered statistically significant.Results: The mean of Reda score in the drug group was 3.433 ± 0.635 on the third day, and 0.773 ± 0.422 on the seventh day, but in the placebo group, it was 5.611 ± 0.492, 2.185 0 0.478, respectively. The two groups had significant difference on the third and seventh days in terms of wound healing (p<0.001).  The median McGill score in the drug group was 26 on the third day and 7 on the seventh day, but in the placebo group, it was 44 and 19, respectively, and the two groups had a statistically significant difference in terms of pain intensity on the third and seventh day (P<0.001)Conclusion: The use of plantago cream in comparison with placebo increases the speed of improvement of pain intensity and episiotomy wound healing in nulliparous women.